INFORMATION SYSTEM MODEL OF WEBSITE-BASED TAX PAYMENT AND VILLAGE BUILDING - Verry Ronny Palilingan (Program Studi Pendidikan Teknologi Informasi dan Komunikasi, Universitas Negeri Manado, 2021)
Property tax is one of the instruments in obtaining funding for village development. Property tax proceeds are used to finance development in the area. Good management is needed to maximize property tax revenue. This study aims to help the model to design and develop an e-village property tax information system. the method used is the description method and is used to model the system while the prototype method is used to build the e-village system. The testing stage uses the black box technique and the usability test to test the quality, usability, and reliability of the system functions that have been made. This research succeeded in building an e-village model that is efficient and can be used easily to carry out property tax transactions. the results of this study also help villagers easily obtain information and assist in the processing of village data that is structured, organized and to help calculate the amount of property tax costs to be paid. The conclusion of this study is that the system has been made to facilitate the community and village officials in calculating the property tax, managing and obtaining village information more effectively and efficiently.